Pristimerin Suppresses Trophoblast Cell Epithelial–Mesenchymal Transition via miR-542-5p/EGFR Axis - Shu C; Yu X; Cheng S; Jing J; Hu C; Pang B (Dove Medical Press, 2020)
Chang Shu,1,* Xiaowei Yu,2,* Shihuan Cheng,3 Jili Jing,2 Cong Hu,2,3 Bo Pang4,5 1Department of Obstetrics and Gynecology, The First Hospital of Jilin University, Changchun, Jilin 130021, People’s Republic of China; 2Centre for Reproductive Medicine, Centre for Prenatal Diagnosis, The First Hospital of Jilin University, Changchun, Jilin 130021, People’s Republic of China; 3Department of Rehabilitation, The First Hospital of Jilin University, Changchun, Jilin 130021, People’s Republic of China; 4Central Laboratory, The First Hospital of Jilin University, Changchun, Jilin 130021, People’s Republic of China; 5Department of Cardiology, The First Hospital of Jilin University, Changchun, Jilin 130021, People’s Republic of China*These authors contributed equally to this workCorrespondence: Cong Hu; Bo Pang Email conghu@jlu.edu.cn bopang@jlu.edu.cnBackground: Ectopic pregnancy (EP) is an ectopic embryo implantation occurred outside the uterine cavity. Nowadays, more attention have garnered in fast and effective treatment with less side effects. Pristimerin is known as the clinical application for anti-cancer, and the effect on EP therapy is still unclear.Materials and Methods: Trophoblast cell line HTR-8/SVneo was used; then, we performed cell counting kit-8 assay, wound healing assay, flow cytometry and real-time polymerase chain reaction analysis (RT-PCR) to detect the cell viability, migration ability, apoptosis and epithelial–mesenchymal transition (EMT) under pristimerin treatment. In addition, public bioinformatic database was used to discover the connection between molecular and genes. Finally, we used miRNA transfection and RT-PCR techniques to determine the underlying molecular mechanism.Results: We revealed that pristimerin inhibited trophoblast cells proliferation, migration and EMT, while induced trophoblast cell apoptosis. Furthermore, expression of miR-542-5p, AGO2 and EGFR was suppressed in HTR-8/SVneo cells post pristimerin treatment, and miR-542-5p silence showed the same effect. Combing pristimerin treatment and miR-542-5p silence showed a synergistic action.Conclusion: Pristimerin could be an effective treatment to block embryo implantation by miR-542-5p and EGFR down-regulation.Keywords: pristimerin, trophoblast cell, unruptured ectopic pregnancy, miR-542-5p, EGFR